Hadith #746 - Sahih al-Bukhari - Marwan bin al-Hakam bin Abi al-'As (Sahih al-Bukhari)
Zaid bin Thabit said to me, “Why do you recite very short Suras in the Maghrib prayer while I heard the Prophet (ﷺ) reciting the longer of the two long Suras?”
Grade: Sahih

Hadith #1509 - Sahih al-Bukhari - Marwan bin al-Hakam bin Abi al-'As (Sahih al-Bukhari)
I saw `Uthman and `Ali. `Uthman used to forbid people to perform Hajj-at-Tamattu` and Hajj-al- Qiran (Hajj and `Umra together), and when `Ali saw (this act of `Uthman), he assumed Ihram for Hajj and `Umra together saying, “Lubbaik for `Umra and Hajj,” and said, “I will not leave the tradition of the Prophet (ﷺ) on the saying of somebody.”
Grade: Sahih

Hadith #3557 - Sahih al-Bukhari - Marwan bin al-Hakam bin Abi al-'As (Sahih al-Bukhari)
`Uthman bin `Affan was afflicted with severe nose-bleeding in the year when such illness was prevelant and that prevented him from performing Hajj, and (because of it) he made his will. A man from Quraish came to him and said, “Appoint your successor.” `Uthman asked, “Did the people name him? (i.e. the successor) the man said, “Yes.” `Uthman asked, “Who is that?” The man remained silent. Another man came to `Uthman and I think it was Al-Harith. He also said, “Appoint your success
Grade: Sahih

Hadith #3558 - Sahih al-Bukhari - Marwan bin al-Hakam bin Abi al-'As (Sahih al-Bukhari)
While I was with `Uthman, a man came to him and said, “Appoint your successor.” `Uthman said, “Has such successor been named?” He replied, “Yes, Az-Zubair.” `Uthman said, thrice, “By Allah! Indeed you know that he is the best of you.”
Grade: Sahih

Hadith #446 - Sunan al-Nasa'i - al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Marwan bin al-Hakam bin Abi al-'As; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Urwa ibn al-Zubayr عروة بن الزبير (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘Whoever touches his private part, let him perform Wudu’.'”
Grade:

Hadith #990 - Sunan al-Nasa'i - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Marwan bin al-Hakam bin Abi al-'As; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Urwa ibn al-Zubayr عروة بن الزبير; Zayd ibn Thabit (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) recited ‘Ha- Mim Ad-Dukhan’ in Maghrib.
Grade:

Hadith #1543 - Sunan al-Nasa'i - Abdullah bin Yazid al-'Advi عبد الله بن يزيد العدوي المقري القصير; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Marwan bin al-Hakam bin Abi al-'As; Urwa ibn al-Zubayr عروة بن الزبير (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) led one of the two groups in praying one rak’ah while the other group was facing the enemy, then they moved away and took the place of the others, and the others came and he led them in praying the other rak’ah, then he said the salam and they stood up and made up the other rak’ah, and the others stood up and made up the other rak’ah.
Grade:

Hadith #2722 - Sunan al-Nasa'i - Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Marwan bin al-Hakam bin Abi al-'As; Muslim bin 'Imran al-Batayn مسلم بن عمران البطين; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“We went out with the Messenger of Allah around the time of the new moon of Dhul-Hijjah, and the Messenger of Allah said: ‘Whoever wishes to enter Ihram for Hajj, let him do so , and whoever wishes to enter Ihram for ‘Umrah, let him do so'”
Grade:

Hadith #2765 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Miswar bin Makhrama bin Nawfal; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibn Ishaq محمد بن إسحاق بن يسار‎; Marwan bin al-Hakam bin Abi al-'As; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came out in the year of al-Hudaibbiyyah with over ten hundreds of Companions and when he came to Dhu al Hulaifah. He garlanded and marked the sacrificial animals, and entered the sacred state of Umrah. He then went on with the tradition. The Prophet moved on and when he came to the mountain, pass by which one descends (to Mecca) to them, his riding-beast knelt down, and the people said twice: Go on, go on, al-Qaswa has become jaded. The Prophet (May peace be upon him
Grade: Sahih

Hadith #5008 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abdur Rahman bin al-Aswad; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Marwan bin al-Hakam bin Abi al-'As; Ubayy ibn Ka'b; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
It would have been better for him. I heard the Messenger of Allah (ﷺ) say: I think (or, I have been commanded) that I should be brief in what I say, for brevity is better.
Grade: Hasan

Hadith #3202 - Jami' al-Tirmidhi - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; al-Hasan bin Muhammad al-Za'farani الحسن بن محمد الصباح الزعفراني; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ibn Jurayj ابن جريج; Marwan bin al-Hakam bin Abi al-'As (Jami' al-Tirmidhi)
“I entered upon Mu’awiyah and he said:’ Shall I not give you some good news?’ I said: ‘Of course!’ He said: ‘I heard the Messenger of Allah (ﷺ) saying: ‘Talhah is among those who fulfilled their vow.'”
Grade:

Hadith #517 - Sunan Ibn Majah - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Busra bint Safwan bin Nawfal; Hisham bin 'Urwa هشام بن عروة; Marwan bin al-Hakam bin Abi al-'As; Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“There was a man among the Ansar whose house was the furthest house in Al-Madinah, yet he never missed prayer with the Messenger of Allah. I felt sorry for him and said: ‘O so-and-so, why do you not buy a donkey to spare yourself the heat of the scorching sand, to carry over the stony ground, and to keep you away from the vermin on the ground?’ He said: ‘By Allah! I do not want to live so close to Muhammed.’ This troubled me until I came to the house of the Prophet and mentioned that t
Grade: